An empirical study of trade dynamics in the fed funds market - Gara Afonso; Ricardo Lagos (Federal Reserve Bank of New York, 2012)
We use minute-by-minute daily transaction-level payments data to document the crosssectional and time-series behavior of the estimated prices and quantities negotiated by commercial banks in the fed funds market. We study the frequency and volume of trade, the size distribution of loans, the distribution of bilateral fed funds rates, and the intraday dynamics of the reserve balances held by commercial banks. We fi nd evidence of the importance of the liquidity provision achieved by commercial banks that act as de facto intermediaries of fed funds.
Keywords: E42; E44; G21; 330; monetary policy; fed funds market; fed funds rate